2003
DOI: 10.1128/aac.47.2.747-754.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Can Exert a Modest Antiviral Effect against Human Immunodeficiency Virus Type 1 Containing the M184V Mutation

Abstract: The M184V mutation in human immunodeficiency virus (HIV) reverse transcriptase is associated with high-level resistance to both (؊)2,3-dideoxy-3-thiacytidine (3TC) and (؊)2,3-dideoxy-5-fluoro-3-thiacytidine as well as low-level resistance to 2,3-dideoxyinosine, 2,3-dideoxycytidine, and abacavir. This mutation is also associated with diminished HIV replicative fitness as well as several functional changes in enzyme activity, including diminutions in polymerase processivity, pyrophosphorylysis, and nucleotide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
(50 reference statements)
4
29
0
Order By: Relevance
“…3D and 4). This finding is in line with those of Quan et al in cell-free RT assays and in PBMC (58) and with those of Aquaro et al (5), who found that the emergence of 3TC resistance in culture through acquisition of the M184V mutation is significantly slower and more difficult in MDMs than in other cell types. Although this latter finding could be related to an intrinsic lower rate of viral replication in MDMs, it may pertain to the fact that in these cells the selective advantage conferred by the M184V mutation, even in the presence of 3TC, is smaller than in other cell types.…”
Section: Vol 81 2007supporting
confidence: 81%
See 1 more Smart Citation
“…3D and 4). This finding is in line with those of Quan et al in cell-free RT assays and in PBMC (58) and with those of Aquaro et al (5), who found that the emergence of 3TC resistance in culture through acquisition of the M184V mutation is significantly slower and more difficult in MDMs than in other cell types. Although this latter finding could be related to an intrinsic lower rate of viral replication in MDMs, it may pertain to the fact that in these cells the selective advantage conferred by the M184V mutation, even in the presence of 3TC, is smaller than in other cell types.…”
Section: Vol 81 2007supporting
confidence: 81%
“…For d4T, the mean IC 50 to 0.359 M in MDMs pretreated for 16 h. For 3TC, the mean IC 50 was fivefold lower in MDMs than in P4 cells ( Fig. 2 and Table 1) in accordance with what has been previously described in a study performed in PBMC (58). Taken together, these data illustrate the impact of the cellular context on the antiviral activity of some NRTIs such as d4T, ddI, and 3TC.…”
Section: Susceptibility Of Wt Nl4-3 To Nrtis In Mdmssupporting
confidence: 79%
“…Early observations of viral load rebound during lamivudine monotherapy and lamivudine-containing regimens demonstrated that plasma HIV-1 RNA concentrations remained lower than pretherapy levels despite the uniform presence of M184V in plasma viruses (132,153). However, other studies have shown that lamivudine does exert some antiretroviral effect on the M184V mutant, suggesting that the incomplete viral rebounds that occur may represent residual antiviral activity rather than selection for a mutant with reduced fitness (139). Studies of selective lamivudine treatment interruptions demonstrate increases in viral load before reversion of the M184V mutant, also supporting the hypothesis that lamivudine retains antiretroviral activity against M184V (28).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%
“…An in vitro antiviral selectivity assay was conducted against human immunodeficiency virus (HIV) as follows (17). Cord blood mononuclear cells were infected with HIV type 1 IIIb (laboratory strain) for 2 h. The free virus was washed off, and the cells were transferred to plates.…”
Section: Antiviral Analysismentioning
confidence: 99%
“…The compounds were added as a solution in water. Following 7 days of incubation in culture, the reverse transcriptase (RT) activity of the supernatant was measured to determine antiviral activity as previously described (17). Selectivity assays against other viruses were performed using standard cytopathic effect assays as previously described (7).…”
Section: Antiviral Analysismentioning
confidence: 99%